Glutamine synthetase in the phloem plays a major role in controlling proline production - Brugiere, N (1999)
To inhibit expression specifically in the phloem, a 274-bp fragment of a cDNA (Gln1-5) encoding cytosolic glutamine synthetase (GS1) from tobacco was placed in the antisense orientation downstream of the cytosolic Cu/Zn superoxide dismutase promoter of Nicotiana plumbaginifolia. After Agrobacterium-mediated transformation, two transgenic N. tabacum lines exhibiting reduced levels of GS1 mRNA and GS activity in midribs, stems, and roots were obtained. Immunogold labeling experiments allowed us to verify that the GS protein content was markedly decreased in the phloem companion cells of transformed plants. Moreover, a general decrease in proline content in the transgenic plants in comparison with wild-type tobacco was observed when plants were forced to assimilate large amounts of ammonium. In contrast, no major changes in the concentration of amino acids used for nitrogen transport were apparent. A (15)NH(4)(+)-labeling kinetic over a 48-hr period confirmed that in leaves of transgenic plants, the decrease in proline production was directly related to glutamine availability. After 2 weeks of salt treatment, the transgenic plants had a pronounced stress phenotype, consisting of wilting and bleaching in the older leaves. We conclude that GS in the phloem plays a major role in regulating proline production consistent with the function of proline as a nitrogen source and as a key metabolite synthesized in response to water stress.